Productivity of Thin Fiber Cotton Varieties Under Conditions of Stress Factors (Texas Journal of Agriculture and Biological Sciences, 2023)
The article presents the data obtained on the study of yield and quality indicators of different thinfibre cotton varieties. The number of crop elements, crop weight and quality indicators were determined in all varieties. Based on the mentioned results, it was noted that the above parameters change in various degrees in the section of the varieties and are related to the biological and variety characteristics of the varieties.